AN ANALYSIS OF ENGLISH-INDONESIA TRANSLATION PROCEDURES ON GOOGOLE MAIL WEB PAGES - Nugraha, Mokhamad Bagja (2015)
This research aims to find out the translation quality and translation procedures in Google Mail Web Pages based on the theories proposed by Newark (1988), Larson (1984), Vinay and Darbelnet (1973) and Catford (1965). This research uses a qualitative case study approach proposed by Stake (1995, cited in Hyett, 2014, p. 2; cited in Creswell, 2003, p. 15), and Yin (2003, cited in Baxter and Jack, 2008, p. 548) and uses the interview method proposed by Frankael, Wallen, and Hyun (2012) in order to find out the responses toward the Translation of Google Mail Web Pages. There are four interviewee who are majoring Translating class were interviewed in this research in order to get the information whether the translations were acceptable or not The data shows that there are 370 phrases from the 21 selected pages in Google Mail Web Pages with the most frequently used is Literal translation procedure (34.53%), Couplet and Triplet (30.54%), Cultural Equivalent (14.05%), Naturalization (7,57%), Shift or Transposition (5,68%), Transference or Borrowing (4,32%), and Reduction and Expansion (3,24%). . All of participants also express that the translation of Google Mail Web Pages is acceptable. Keywords: Translation, Procedures, Google Mail Web Pages, Translation Quality